A New Daphne Diterpenoids from Daphne acutiloba Rehd. - Xu, Yi-Ran; Li, Yin-Ke; Cao, Jing-Li; Zhang, Xin; Yang, Guang-Yu; Hu, Qiu-fen (Asian Journal of Chemistry, 2010)
A new daphne diterpenoid (daphnediterp A) was isolated from the leaf and steam of Daphne acutiloba Rehd. Its structure was determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. The anti HIV-1 activity was also evaluated and it shows an anti HIV-1 activity with a therapeutic index above 31.4.